Integrated control strategy of apple scab according to warning equipment - L. Raudonis (Plant Protection Science, 2002)
In 1999-2001 in field trials two different apple scab control strategies were compared: (i) the current strategy - conventional disease management (CDM) and (ii) integrated disease management (IDM), according to scab infection periods. A new scab warning equipment METOSR-D was used for detection of infection periods and forecast of disease intensity at three levels: light, moderate and severe. According to CDM apple-trees were sprayed 9 times a season. Scab warning equipment gave a possibility to optimize the use of fungicides against scab and to reduce the total spray applications per season in average till 6.3 in very susceptible cultivars and 5 in moderately susceptible ones. This is 30 and 44% less spray applications comparing with CDM. Annual spray program ranged from 5 till 8 spray applications of very susceptible cultivars. CDM and IDM gave high scab control in apple-trees and there was not found any essential difference in scab incidence between two control strategies.